Archaeological Data Models and Web Publication Using XML. - Schloen, J. David (Computers & the Humanities, 2001)
An appropriate standardized data model is necessary to facilitate electronic publication and analysis of archaeological data on the World Wide Web. A hierarchical ``item-based'' model is proposed which can be readily implemented as an Extensible Markup Language (XML) tagging scheme that can represent any kind of archaeological data and deliver it in a cross-platform, standardized fashion to any Web browser. This tagging scheme and the data model it implements permit seamless integration and joint querying of archaeological datasets derived from many different sources.